«Eit givande, men krevjande lagspel for å betre tenestene». Brukarerfaringar frå samarbeidsforsking - Halding, Anne-Grethe; Fossøy, Aud Berit; Moltu, Christian; Grov, Ellen Karine (Nordisk Tidsskrift for Helseforskning, 2016)
“A precious, but challenging teamwork for improved healthcare”. Service users´ experiences from participatory research In spite of identifying the importance of service user (SU) involvement in healthcare research, few studies define specific activities. Although an effective infrastructure is acknowledged as key to enable SU’s equal contribution, we, in Norway, recognize a lack of their involvement in studies on Chronic Obstructive Pulmonary Disease (COPD). Consequently, a preliminary project was designed to implement a research-training programme for co-researchers and seek their collaboration in a participatory research study on COPD. This paper reports the co-researchers’ experiences using a focus group interview. Through content analysis, we describe coresearchers’ experiences, which recognize the importance and challenges of participatory research.These experiences demonstrate how acknowledgement, a fruitful climate for collaboration, new insight and practical arrangements promote involvement, whilst too extensive training and vague expectations may hinder involvement. Empowering equality of relationships and involvement, particularly for co-researchers with failing health and no former research training, demands thorough planning and organizing. Samarbeidspartnarar: brukarar Nina Maria Dolmen, Aud Jenny Jensen, Sissel Stavøstrand og Steinar Valvik, spesialsjukepleiar Grete Berg Grimelid, Helse Førde, ergoterapeut Evy Aarsheim, Flora kommune, og sosionom og PhD stipendiat Tone Larsen, Helse Førde